2004
DOI: 10.1063/1.1786664
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary infrared transmission of Cu-coated arrays with subwavelength apertures: Hole size and the transition from surface plasmonto waveguide transmission

Abstract: Articles you may be interested inPropagation lengths of surface plasmon polaritons on metal films with arrays of subwavelength holes by infrared imaging spectroscopy Influence of unsymmetrical periodicity on extraordinary transmission through periodic arrays of subwavelength holes Appl. Phys. Lett. 90, 161112 (2007); 10.1063/1.2724914 Surface-plasmon resonance with infrared excitation: Studies of phospholipid membrane growth J. Appl. Phys. 98, 093506 (2005); 10.1063/1.2123370 Enhanced infrared absorption spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…An experimental signature for the Fabry-Perot resonances is that they do not respond to angle-tuning, which does influence the surfacewaves coupled to a periodic hole-array. As a result, the angle-tuned dispersion shows a flat-band response, which has been demonstrated for square-hole arrays in the infrared using copper meshes [78], as shown in Fig. 7.…”
Section: Film Thicknessmentioning
confidence: 89%
“…An experimental signature for the Fabry-Perot resonances is that they do not respond to angle-tuning, which does influence the surfacewaves coupled to a periodic hole-array. As a result, the angle-tuned dispersion shows a flat-band response, which has been demonstrated for square-hole arrays in the infrared using copper meshes [78], as shown in Fig. 7.…”
Section: Film Thicknessmentioning
confidence: 89%
“…The electromagnetic wave is confined on the surface and coupled into the hole in the form of SPPs, giving rise to the transmission peaks [11] . As the matching condition above is a rigorous equation the resonant peak is usually rather distinct, which can be seen in Fig.…”
Section: Structure and Simulationmentioning
confidence: 99%
“…The work that has been done in the mid-IR has already demonstrated quite promising results. Meshes and periodic structures utilizing SPs and designed for the mid-IR have been shown to have similar properties to structures in the visible [9][10][11]. In addition, it has also been shown that chemical attachment to the mesh surface can enhance the sensitivity of molecular absorption measurements by several orders of magnitude [10].…”
Section: Introductionmentioning
confidence: 96%